IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Muhammad Yunus; Anis Zohriah; Anis Fauzi (Kelola: Journal of Islamic Education Management, 2022)
This study aims to understand and analyze: (1) Implementation of Supervision by the Principal in Improving Teacher Performance, (2) Stages of implementing academic supervision in improving teacher performance, (3) The constraints faced in the implementation of academic supervision by school principals in improving teacher performance in SMP Negeri 1 Mancak, SMP Negeri 2 Anyar and SMP Negeri 1 Gunungsari. This study uses a qualitative approach to the type of comparative study. Data collection methods are observation, interview and documentation. Data analysis techniques through the process of data reduction, the process of presenting data and the process of drawing conclusions. The results showed that (1) The Implementation of Academic Supervision by the School Principals was carried out well and planned, so as to improve teacher performance. (2) The stages carried out in supervision include (a) the planning phase, (b) the implementation phase and (c) the follow-up stage. (3) the constraints faced in the implementation of academic supervision in improving teacher performance in Mancak 1 Junior High School, 2 Anyar Junior High School and Gunungsari 1 Junior High School are time, teacher readiness and the technique of Making Learning Implementation Plans.